Undoped and Manganese2+-doped polycrystalline Cd1-xInxTe sensitizer for liquid-junction solar cell devices - Singsa-ngah,M. (Academic Press Inc., 2015)
© 2015 Elsevier Inc. Ternary Cd1-xInxTe semiconductor nanoparticles have been demonstrated to be sensitizers for solar cell devices. The chemical bath deposition (CBD) process was used to synthesize Cd1-xInxTe nanoparticles, which were deposited onto a mesoporous TiO2 photoelectrode. Individual nanoparticles were estimated to have an average diameter range of ~10nm. The atomic percentages of chemical elements for Mn2+-doped Cd1-xInxTe show that the structure could be Mn2+-doped CdInTe incorporated with CdIn2Te4 structure. The resulted X-ray diffraction and diffraction ring patterns of Mn2+-doped Cd1-xInxTe nanoparticles indicated the structure to be tetragonal. The optical band gaps were also decreased to 0.9eV after Mn2+ doping, compared with Eg=1.47eV for undoped Cd1-xInxTe(7). The best efficiency of 0.51% under 100 mW/cm2 (AM 1.5G) was obtained after Mn2+ doping with a short-circuit current density (Jsc) of 1.71mA/cm2, an open-circuit voltage (Voc) of 0.739V and a fill factor (FF) of 40.2%. This work demonstrated the feasibility of using Cd1-xInxTe with Mn2+ doping as a broadband solar absorber for TiO2 photoelectrodes.